Antibiotic treatment of bacterial vaginosis to prevent preterm delivery: Systematic review and individual participant data meta‐analysis. Issue 3 (18th January 2023) - Klebanoff, Mark A.; Schuit, Ewoud; Lamont, Ronald F.; Larsson, Per‐Göran; Odendaal, Hein J.; Ugwumadu, Austin; Kiss, Herbert; Petricevic, Ljubomir; Andrews, William W.; Hoffman, Matthew K.; Shennan, Andrew; Seed, Paul T.; et al.
Abstract: Background: Bacterial vaginosis (BV) increases preterm delivery (PTD) risk, but treatment trials showed mixed results in preventing PTD. Objectives: Determine, using individual participant data (IPD), whether BV treatment during pregnancy reduced PTD or prolonged time‐to‐delivery. Data Sources: Cochrane Systematic Review (2013), MEDLINE, EMBASE, journal searches, and searches (January 2013–September 2022) ("bacterial vaginosis AND pregnancy") of (i) clinicaltrials.gov ; (ii) Cochrane Central Register of Controlled Trials; (iii) World Health Organization International Clinical Trials Registry Platform Portal; and (iv) Web of Science ("bacterial vaginosis"). Study Selection and Data Extraction: Studies randomising asymptomatic pregnant individuals with BV to antibiotics or control, measuring delivery gestation. Extraction was from original data files. Bias risk was assessed using the Cochrane tool. Analysis used "one‐step" logistic and Cox random effect models, adjusting gestation at randomisation and PTD history; heterogeneity by I 2 . Subgroup analysis tested interactions with treatment. In sensitivity analyses, studies not providing IPD were incorporated by "multiple random‐donor hot‐deck" imputation, using IPD studies as donors. Results: There were 121 references (96 studies) with 23 eligible trials (11, 979 participants); 13 studies (6915 participants) provided IPD; 12 (6115) were incorporated. Results from 9 (4887 participants) not providing IPD were imputed. Odds ratios for PTD for metronidazole and clindamycin versus placebo were 1.00 (95% CI 0.84, 1.17), I 2 = 62%, and 0.59 (95% CI 0.42, 0.82), I 2 = 0 before; and 0.95 (95% CI 0.81, 1.11), I 2 = 59%, and 0.90 (95% CI: 0.72, 1.12), I 2 = 0, after imputation. Time‐to‐delivery did not differ from null with either treatment. Including imputed IPD, there was no evidence that either drug was more effective when administered earlier, or among those with a PTD history. Conclusions: Clindamycin, but not metronidazole, was beneficial in studies providing IPD, but after imputing data from missing IPD studies, treatment of BV during pregnancy did not reduce PTD, nor prolong pregnancy, in any subgroup or when started earlier in gestation.